Penerapan Tata Kelola Kearsipan Pada PT. Sekar Bumi Alam Lestari, Kecamatan Tapung Hilir, Kabupaten Kampar - Anggi Afriana Putri; Desvi Emti (Yayasan Almanar Pujud, 2025)
This study highlights how PT. Sekar Bumi Alam Lestari in Kampar Regency manages its important archives amidst the technological challenges and resource constraints still frequently faced by many companies in Indonesia. As a palm oil company, PT. Sekar Bumi Alam Lestari has a large and diverse volume of documents, making archive management crucial. This research focuses on the implementation of archival governance, from incoming mail management, storage, maintenance, and the archive destruction process. Through interviews with archive staff and direct observation, it was discovered that the company implements a combination of centralized and decentralized management systems, with subject-based storage and the archive destruction process carried out by incineration. Although archive maintenance remains simple, the company strives to adhere to existing standard procedures to ensure orderly and effective document management.